Explaining International Acts - Keitner, Chimène (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2018)
This contribution to the symposium on Evan Criddle & Evan Fox-Decent’s “Fiduciaries of Humanity” pushes against the strong claim by some critics that international legal norms are concerned solely with outcomes, rather than with processes of deliberation and justification more commonly associated with certain areas of domestic law. It explores this proposition by looking at examples including the 1999 Kosovo intervention, the April 2018 Syria strikes, and the results of the Chilcot Inquiry in the United Kingdom. Although deliberative processes that lead to international acts may not be judicially reviewable to the same extent as those that lead to purely domestic acts, the push for “transparency” among domestic constituencies, as well as other oversight mechanisms, create ex ante incentives for integrity in decision-making processes and rationales in the conduct of foreign affairs. In addition, ex post explanations of international acts may themselves carry legal significance as expressions of a state’s opinio juris. Scholars and practitioners should not discount the “culture of justification” that exists at the international level, even outside international courts and tribunals.